Nuclear Factor-κB Plays a Positive Role in TNFα Expression in Golden Pompano, Trachinotus ovatus (Linnaeus 1758) - Zhu, Ke-Cheng; Guo, Hua-Yang; Guo, Liang; Liu, Bao-Suo; Zhang, Nan; Jiang, Shi-Gui; Zhang, Dian-Chang (Frontiers in Marine Science, 2022)
Tumor necrosis factor-α (TNFα) is a multifarious mediator of lymphoid tissue growth, anti-microbial defense mechanisms, and a regulator of pro-inflammatory. The function of TNFα in parasite infection and detailed mechanism through which nuclear factor-κB (NF-κB) regulates TNFα remain largely indistinct in teleost. In the present study, the identification of TNFα (ToTNFα) from golden pompano (Trachinotus ovatus) and its sequence features and expression levels were performed. The genomic DNA sequence is composed of 1,130 bp, consists of 4 exons and 3 introns, and encodes for 341 amino acid polypeptides. The putative protein sequence shares 34.7%-61.9% identity to fish TNFα and possesses a TNF family signature and two conserved cysteine residues. Moreover, the expressions of ToNF-κB and ToTNFα are constitutively expressed in all examined tissues, with higher levels observed in the immune relevant tissues. Both of the ToNF-κB and ToTNFα transcriptions were increased in the local infection sites (skin and gill) and system immune tissues (liver, spleen and head-kidney) after Cryptocaryon irritans stimulation. In addition, to investigate whether ToNF-κB is a regulator of ToTNFα, promoter analysis is performed. The region from -970 bp to +79 bp is known as the core promoter by diﬀerent truncated mutants of ToTNFα. Subsequently, the activity of the ToTNFα-p2 promoter was dramatically reduced after targeted mutation of M6-binding site. Additionally, electrophoretic mobile shift assay (EMSA) verified that ToNF-κB interacted with the M6-binding site in the ToTNFα promoter region to control the expression of ToTNFα. In conclusion, the present study provides the positive regulation of TNFα transcription by NF-κB and contributes to a better understanding of the transcriptional mechanism of TNFα in fish.